A steel ball with a diameter of 110 mm or more and a method for manufacturing the steel ball

CN122358047BActive Publication Date: 2026-10-16CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610789851.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-16
Estimated Expiration
2046-06-03

AI Technical Summary

Technical Problem

然而,该钢球中C含量高,C易偏析,形成大尺寸碳化物,容易造成冲击疲劳破坏,Mn含量超过1.2%,容易造成偏析并增加开裂倾向,同时也会增加淬火过程中残余奥氏体量,使磨球硬度降低

Benefits of technology

[0017]本发明的直径110mm以上研磨钢球及钢球的制备方法与现有技术相比,具有以下有益效果中的至少一种:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122358047B_ABST
    Figure CN122358047B_ABST
Patent Text Reader

Abstract

The present application relates to the field of metal material, and discloses a kind of steel ball of grinding above 110mm in diameter and a preparation method of steel ball.The steel ball composition includes C:0.68%~0.78%, Si:0.25%~0.45%, Mn:0.85%~1.05%, Cr:0.55%~0.75%, Ni:0.3%~0.4%, Mo:0.04%~0.06%, V:0.04%~0.06%, the rest is Fe and inevitable impurities, the surface layer structure of steel ball is tempered martensite, and the core structure includes tempered martensite and bainite.The steel ball composition of the present application cooperates with its preparation process, realizes the effect of quenching not cracking, storage not cracking and impact not easy to crack in ore grinding service, and the whole cross-section hardness difference is small, the hardness is high, and the toughness is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metallic materials, specifically to a grinding steel ball with a diameter of 110 mm or more and a method for preparing the steel ball. Background Technology

[0002] Grinding steel balls are the most important grinding media consumable in ball mills used in mining. Grinding steel balls with a diameter of 110mm or more are considered large-sized grinding steel balls, mainly used for crushing and coarse grinding of large pieces of ore. During service, the steel balls must withstand high-frequency, high-intensity impact loads and long-term, high-stress abrasive wear, especially in large semi-autogenous mills or ball mills, where the steel balls undergo violent collisions during impact. Therefore, large-sized grinding steel balls not only require high surface hardness to resist grinding wear, but also must possess excellent impact toughness and fatigue resistance to ensure that they do not break or prematurely peel off under repeated impacts, thereby extending their service life and reducing wear.

[0003] For large grinding steel balls with a diameter of 110mm or more, the increased heat transfer from the core to the surface during quenching results in a cooling rate in the core that is far lower than the critical quenching rate of the steel. This makes it easier for the core to enter the pearlite transformation zone, leading to the formation of a large amount of pearlite soft phase in the core. Simultaneously, the surface of the steel ball, due to its close contact with the quenching medium, cools rapidly, resulting in a high-hardness martensitic structure. This creates a typical "hard shell, soft core" microstructure, with the hardness difference between the surface and core reaching up to 15 HRC. This significant hardness gradient means that while the hard outer shell provides some wear resistance during service, the soft core cannot provide sufficient impact and deformation resistance. Under high-frequency, high-intensity impact loads from large pieces of ore, the soft core is prone to plastic deformation and fatigue cracking. These cracks gradually propagate, eventually causing the entire steel ball to peel off or break, significantly increasing wear and drastically shortening its service life.

[0004] Patent CN107739986A discloses a large-diameter forged wear-resistant steel ball for mining applications. Its chemical composition by weight percentage includes: C: 0.8%~1.2%, Si: 0.6%~0.9%, Mn: 1.2%~1.5%, Cr: 1.0%~1.5%, Mo: 0.1%~0.3%, V: 0.05%~0.15%, Ti: 0.1%~0.2%, Al: 0.05%~0.15%, Cu: 0.05%~0.15%, Zr: 0.05%~0.15%, Hf: 0.05%~0.15%, B: 0.08%~0.2%, P≤0.02%, S≤0.01%, with the remainder being Fe and unavoidable impurities. By adding hardenability-enhancing elements such as Mn, Mo, Cr, V, Ti, and Cu, this steel ball can increase the stability of supercooled austenite and improve the hardenability of the steel, reducing the difference in hardness between the core and surface of large-diameter grinding balls. However, the high carbon content in this steel ball makes it prone to segregation, forming large-sized carbides that easily cause impact fatigue failure. The Mn content exceeding 1.2% also easily causes segregation and increases the tendency to crack, while simultaneously increasing the amount of residual austenite during quenching, thus reducing the hardness of the grinding ball.

[0005] Therefore, there is an urgent need in this field to study the alloy composition and supporting preparation process of large-sized grinding steel balls with a diameter of 110 mm or more, in order to solve the problems of cracking during processing and service and the large difference in strength and toughness between the surface and the core of large-sized grinding steel balls with a diameter of 110 mm or more. Summary of the Invention

[0006] In view of the above-mentioned problems in the prior art, the main objective of the present invention is to provide a grinding steel ball with a diameter of 110 mm or more and a method for preparing the steel ball.

[0007] According to one aspect of the present invention, a grinding steel ball with a diameter of 110 mm or more is provided, the steel ball comprising the following components by mass percentage: C: 0.68%~0.78%, Si: 0.25%~0.45%, Mn: 0.85%~1.05%, Cr: 0.55%~0.75%, Ni: 0.3%~0.4%, Mo: 0.04%~0.06%, V: 0.04%~0.06%, with the remainder being Fe and unavoidable impurities, the surface microstructure of the steel ball being tempered martensite, and the core microstructure comprising tempered martensite and bainite.

[0008] According to one embodiment of the present invention, the steel ball comprises the following components by mass percentage: C: 0.73%, Si: 0.35%, Mn: 0.95%, Cr: 0.65%, Ni: 0.35%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities.

[0009] According to another aspect of the present invention, a method for preparing grinding steel balls with a diameter of 110 mm or more is provided. The method is used to prepare grinding steel balls as described in any of the above embodiments, and the method includes the following steps: The steel balls are smelted according to the target composition and continuously cast and rolled into billets of predetermined specifications. The billet is subjected to segmented controlled cooling, wherein the segmented controlled cooling includes: The billet is cooled to a first temperature at a first cooling rate, the first cooling rate being higher than the critical cooling rate for pearlite transformation, and the first temperature being higher than the bainite transformation start temperature. The billet is cooled to room temperature using a second cooling rate, which is within the bainite transformation cooling rate range. According to the target diameter of the steel ball, the billet is cut into equal volume segments, and the steel segments are heated to austenitize and then forged into steel ball blanks at a third temperature, wherein the third temperature is in the two-phase region of austenite and ferrite. The steel ball blank is placed in water for quenching, and the steel ball is removed from the water when the surface temperature of the steel ball reaches a fourth temperature, which is between the martensitic transformation start temperature and the martensitic transformation end temperature. The quenched steel ball blank is then heated and tempered.

[0010] According to one embodiment of the present invention, the final rolling temperature is 800~850°C.

[0011] According to one embodiment of the present invention, the diameter of the pre-defined bar billet is 70-80 mm, the target diameter of the steel ball is 110-150 mm, and the diameter of the bar billet and the target diameter of the steel ball make the axial forging ratio of the steel segment to the steel ball blank 1.5-3.0.

[0012] According to one embodiment of the present invention, the first cooling rate is 1.5~2.5℃ / s, the first temperature is 350~400℃, and the second cooling rate is 0.3~0.8℃ / s.

[0013] According to one embodiment of the present invention, the temperature for heating and austenitizing the steel segment is 900~950℃, and the holding time is 5~10min.

[0014] According to one embodiment of the present invention, the third temperature is 740~760°C.

[0015] According to one embodiment of the present invention, the fourth temperature is 130~170°C.

[0016] According to one embodiment of the present invention, the tempering temperature is 200~250℃ and the holding time is 5~10h.

[0017] Compared with the prior art, the grinding steel ball with a diameter of 110 mm or more of the present invention and the method for preparing the steel ball have at least one of the following beneficial effects: (1) This invention optimizes the alloy composition and proportion of the steel ball, and achieves the dual effects of hardenability and stress regulation through the synergistic effect of elements, thus realizing multiple breakthroughs in the uniformity of steel ball hardness, crack resistance and fatigue toughness, while taking into account both high wear resistance and high toughness. (2) In the method for preparing steel balls of the present invention, after rolling into a billet, the high-temperature stage is first rapidly cooled at a cooling rate higher than the critical cooling rate of pearlite transformation. Combined with the high hardenability composition design, it is ensured that there is no pearlite transformation throughout the process, and all supercooled austenite is maintained to suppress pearlite transformation. The medium-temperature to low-temperature slow cooling promotes uniform bainite phase transformation throughout the entire length and cross-section of the billet. The core cools more slowly, and the volume fraction of bainite is higher than that of the surface layer. Through bainite nucleation and self-catalysis, a refined structure is obtained, and the austenite grains are divided, so that the original austenite grain structure is significantly refined during the subsequent hot working, laying the foundation for obtaining the final refined structure. (3) In the method for preparing steel balls of the present invention, the steel segments cut into equal volumes are processed with a large forging ratio. The initial structure is broken by large deformation and more crystal defects are introduced to fully refine the grains, while ensuring stable forming and high dimensional accuracy. During forging, the forging is carried out in the α+γ two-phase region. Ferrite has poor deformation ability compared with austenite. By introducing ferrite, the number of defects in the deformed austenite and ferrite is increased. High-density defects and distortion can promote recrystallization to form more austenite, refine the austenite grain size, and lay the foundation for obtaining the final refined structure. (4) In the method for preparing steel balls in this invention, the water temperature for quenching the steel ball blank is controlled between the temperature at which the surface temperature of the steel ball reaches the start temperature and the end temperature of the martensitic transformation. This temperature is the temperature range where the martensite transformation is not complete. The surface martensite transformation is controllable and the stress is low, ensuring that the quenching does not crack. The core temperature is high, the martensite transformation is insufficient, the content of retained austenite is high, and the volume fraction of martensite in the core is low. During the subsequent low-temperature tempering heat treatment, the retained austenite enriched in the core is transformed into bainite. This process can eliminate structural stress, offset the martensitic expansion stress, and improve toughness, making the steel ball less prone to cracking even under strong impact during service. Moreover, due to the small size of the original austenite grains, there are many nucleation sites for bainite nucleation from the austenite grain boundaries and during autocatalytic growth. The resulting bainite grains are small and have many grain boundaries, filling the strength gap caused by insufficient martensite in the core, achieving consistent surface and core hardness with a difference of less than 2 HRC. At the same time, due to the refined structure and small grain size, its toughness and strength can also be improved. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 A flowchart illustrating a method for preparing grinding steel balls with a diameter of 110 mm or more according to an embodiment of the present invention is shown; Figure 2 A tensile strength test diagram of a steel ball according to Embodiment 1 of the present invention is shown; Figure 3 A scanning electron microscope image of the surface tissue of a steel ball according to Embodiment 1 of the present invention is shown; Figure 4 A scanning electron microscope image of the core tissue of a steel ball according to Embodiment 1 of the present invention is shown; Figure 5 A photograph of the average grain size test of a steel ball according to Embodiment 1 of the present invention is shown; Figure 6 A photograph of the average grain size test of the steel ball according to Comparative Example 1 of the present invention is shown; Figure 7 A photograph of the average grain size test of the steel ball according to Comparative Example 2 of the present invention is shown. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0021] Furthermore, the reference to "embodiment" herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0022] It should be understood that the embodiments of the invention shown in the exemplary embodiments are merely illustrative. Although only a few embodiments have been described in detail in this invention, those skilled in the art will readily recognize that various modifications are possible without substantially departing from the teachings of the invention. Accordingly, all such modifications should be included within the scope of the invention. Other substitutions, modifications, variations, and deletions can be made to the design, operating conditions, and parameters of the following exemplary embodiments without departing from the spirit of the invention.

[0023] According to one aspect of the present invention, a grinding steel ball with a diameter of 110 mm or more is provided, the steel ball comprising the following components by mass percentage: C: 0.68%~0.78%, Si: 0.25%~0.45%, Mn: 0.85%~1.05%, Cr: 0.55%~0.75%, Ni: 0.3%~0.4%, Mo: 0.04%~0.06%, V: 0.04%~0.06%, with the remainder being Fe and unavoidable impurities. The surface microstructure of the steel ball is tempered martensite, and the core microstructure includes tempered martensite and bainite.

[0024] This invention optimizes the alloy composition and ratio of the steel ball, and achieves the dual effects of hardenability and stress regulation through the synergistic effect of elements. This results in multiple breakthroughs in the uniformity of hardness, crack resistance and fatigue toughness of the steel ball, while taking into account both high wear resistance and high toughness.

[0025] Carbon content (C) is a key factor determining the martensitic substructure in the quenched microstructure of steel balls. Within the low-to-medium carbon range, the hardness increases significantly with increasing carbon content; however, once the carbon content exceeds a certain range, the increase in hardness diminishes considerably with further increases in carbon content, while the toughness of the steel ball gradually decreases. For steel balls requiring both high hardness and high fracture resistance, excessively high carbon content can easily lead to impact fatigue failure. To improve the hardness and strength of the steel balls while avoiding excessive carbon content that increases the risk of embrittlement and hot cracking, this invention controls the carbon content in the steel balls to 0.68%~0.78%.

[0026] Silicon (Si) is a commonly used alloying element in steel. Adding appropriate amounts of silicon can synergistically improve the hardenability of steel. However, when the silicon content exceeds 0.8%, its effect on improving hardenability is significantly weakened, and it may even exacerbate decarburization and overheating during high-temperature heating, while simultaneously increasing resistance to high-temperature deformation, which is detrimental to steel ball production. Therefore, this invention controls the silicon content in the steel balls to be between 0.25% and 0.45%.

[0027] Manganese (Mn) is the most significant and cost-effective alloying element for improving the hardenability of steel balls, and it is also the most commonly used additive element in steel balls. The amount of manganese added to steel balls typically does not exceed 1.2%. If the manganese content is too high, it can easily cause component segregation and increase the risk of cracking. It also increases the volume fraction of retained austenite after quenching, leading to a decrease in the hardness of the grinding ball. Therefore, this invention controls the manganese content in the steel balls to be between 0.85% and 1.05% to balance its hardenability and reduce the risk of cracking.

[0028] Chromium (Cr) is mainly used in combination with silicon and manganese to further improve the hardenability of steel balls. An appropriate amount of chromium can reduce the tendency of oxidation and decarburization on the steel surface, and also helps improve the corrosion resistance of the steel balls under wet grinding conditions. Simultaneously, it refines the grains, reduces microstructure segregation, and improves the uniformity of the cross-sectional microstructure of the steel balls. Therefore, this invention controls the chromium content in the steel balls to be between 0.55% and 0.75%.

[0029] Nickel (Ni) can improve the hardenability and significantly enhance the toughness of steel balls. Nickel refines grains, lowers the ductile-brittle transition temperature, and enhances the fatigue resistance of steel balls under impact loads. However, excessively high nickel content increases cost and has limited effect on hardness improvement. This invention controls the nickel content to 0.3%~0.4%, working synergistically with elements such as carbon, chromium, and molybdenum to promote bainitic microstructure in the steel ball core and improve overall toughness, thus preventing brittle cracking of large-diameter steel balls during service.

[0030] Mo (molybdenum) can significantly inhibit the pearlite transformation and delay the bainite transformation to a lower temperature range, thereby promoting the formation of fine bainite or bainite / martensite multiphase structures at moderate cooling rates. Simultaneously, molybdenum can strengthen grain boundaries and reduce temper brittleness. This invention controls the molybdenum content in the steel balls to 0.04%~0.06%, achieving the above effects at a lower cost. In synergy with chromium, nickel, and manganese, it ensures that the core of steel balls with a diameter of 110mm or more can obtain a uniform tempered martensite and bainite mixed structure, effectively reducing the hardness difference between the surface and the core.

[0031] Vanadium (V) is a strong carbide-forming element. During heating, it precipitates fine carbide particles in synergy with molybdenum (Mo), pinning grain boundaries and refining austenite grains, thereby improving the strength-toughness balance of steel balls. Vanadium also enhances the tempering stability of steel and inhibits the decrease in hardness during high-temperature tempering. This invention controls the vanadium content at 0.04%~0.06%, working synergistically with elements such as carbon and molybdenum to avoid the formation of large-sized carbides while simultaneously improving resistance to impact fatigue failure.

[0032] In addition, the present invention strictly controls the content of impurity elements, wherein P≤0.015% and S≤0.010%, in order to reduce the tendency of cold brittleness caused by phosphorus and hot brittleness caused by sulfur, and ensure the integrity of the steel ball during quenching and service.

[0033] This invention achieves a balance of hardenability, quenchability, toughness, and crack resistance by comprehensively optimizing the content and ratio of C, Si, Mn, Cr, Ni, Mo, and V, utilizing the synergistic effect of each element. For large-sized grinding steel balls with a diameter of 110mm or more, this composition system, combined with appropriate processing technology, can produce a microstructure with a tempered martensite surface and a core primarily composed of tempered martensite and bainite. The surface hardness reaches 54-56 HRC, the core hardness is not less than 52 HRC, and the hardness difference between the surface and core is controlled within 2 HRC. Simultaneously, the surface impact energy is above 25 J, and the core impact energy is above 28 J. No cracking occurs during quenching, and a single ball can withstand 4500 drop tests without cracking. No cracking occurs throughout the entire process of quenching, tempering, storage, and grinding service. The yield strength is higher than 1800 MPa, and the tensile strength is higher than 2000 MPa.

[0034] In one embodiment of the present invention, the steel ball comprises the following components by mass percentage: C: 0.73%, Si: 0.35%, Mn: 0.95%, Cr: 0.65%, Ni: 0.35%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities. This embodiment, through the synergistic effect of its components, significantly improves the hardenability of large-sized steel balls, effectively suppresses the formation of the pearlite soft phase, controls the surface and core hardness difference to within 1 HRC, achieves a full-section hardness of 55 HRC, a surface impact energy of approximately 27 J or more, a core impact energy of approximately 29 J, a yield strength of up to 1850 MPa, and a tensile strength as high as 2100 MPa.

[0035] According to another aspect of the present invention, a method for preparing grinding steel balls with a diameter of 110 mm or more is provided. This method is used to prepare grinding steel balls as described in any of the above embodiments. Figure 1 As shown, the method generally includes the following steps: Step S1: Smelt the steel balls according to the target composition and continuously cast and roll them into billets of predetermined specifications. Step S2: Perform segmented controlled cooling on the billet. Segmented controlled cooling includes: Step S21: Cool the billet to a first temperature using a first cooling rate, where the first cooling rate is higher than the critical cooling rate for pearlite transformation and the first temperature is higher than the bainite transformation start temperature. Step S22: Cool the billet to room temperature using a second cooling rate, which is within the bainite transformation cooling rate range; Step S3: Cut the billet into equal volume segments according to the target diameter of the grinding steel ball, heat the steel segments to austenitize them, and then press-forge them into steel ball blanks at the third temperature, which is in the two-phase region of austenite and ferrite. Step S4: Place the steel ball blank in water for quenching, and remove it from the water when the surface temperature of the steel ball reaches the fourth temperature, which is between the martensitic transformation start temperature and the martensitic transformation end temperature. Step S5: Heat the quenched steel ball blank for tempering treatment.

[0036] In the method for preparing steel balls according to the present invention, after rolling into a billet, the billet is first rapidly cooled at a cooling rate higher than the critical cooling rate for pearlite transformation during the high-temperature stage. Combined with the high hardenability composition design, this ensures that there is no pearlite transformation throughout the process, and all supercooled austenite is maintained, thus suppressing pearlite transformation. The billet is then slowly cooled from medium to low temperature to promote uniform bainite phase transformation along its entire length and cross-section. The core cools even slower, and the volume fraction of bainite is higher than that of the surface layer. Through bainite nucleation and autocatalysis, a refined microstructure is obtained, and the austenite grains are divided. This results in a significant refinement of the original austenite grain structure during subsequent hot working, laying the foundation for obtaining the final refined microstructure.

[0037] In the method for preparing steel balls according to this invention, the steel segments cut to the same volume are processed with a large forging ratio. This process breaks down the initial microstructure through large deformation and introduces more crystal defects, thus refining the grains while ensuring stable forming and high dimensional accuracy. Forging is performed in the α+γ two-phase region. Ferrite has poorer deformation capacity compared to austenite. By introducing ferrite, the number of defects in the deformed austenite and ferrite is increased. High-density defects and distortion promote recrystallization, forming more austenite and refining the austenite grain size, laying the foundation for obtaining the final refined microstructure.

[0038] In the method for preparing steel balls according to this invention, the water temperature for quenching the steel ball blank is controlled between the martensitic transformation start temperature and the martensitic transformation end temperature on the surface of the steel ball. This temperature is within the incomplete martensitic transformation temperature range, ensuring controllable surface martensitic transformation and low stress, thus preventing cracking during quenching. The core temperature is high, resulting in insufficient martensitic transformation, a high content of retained austenite, and a low volume fraction of martensite in the core. During subsequent low-temperature tempering heat treatment, the retained austenite enriched in the core transforms into bainite. This process eliminates structural stress, counteracts martensitic expansion stress, and improves toughness, making the steel ball less prone to cracking even under strong impacts during service. Furthermore, due to the small size of the original austenite grains, there are numerous nucleation sites for bainite during nucleation and autocatalytic growth from austenite grain boundaries, resulting in small bainite grains with numerous grain boundaries. This fills the strength gap caused by insufficient martensite in the core, achieving consistent surface and core hardness with a difference of less than 2 HRC. At the same time, due to the refined structure and small grain size, its toughness and strength can also be improved.

[0039] The method of the present invention will be described in detail below by way of example.

[0040] In step S1, the steel balls are smelted according to the target composition for grinding and continuously cast and rolled into billets of predetermined specifications. The steel balls comprise the following components by mass percentage: C: 0.68%~0.78%, Si: 0.25%~0.45%, Mn: 0.85%~1.05%, Cr: 0.55%~0.75%, Ni: 0.3%~0.4%, Mo: 0.04%~0.06%, V: 0.04%~0.06%, with the remainder being Fe and unavoidable impurities. Further, the steel balls comprise the following components by mass percentage: C: 0.73%, Si: 0.35%, Mn: 0.95%, Cr: 0.65%, Ni: 0.35%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities.

[0041] There are no special restrictions on smelting in this step; conventional electric furnace smelting and vacuum degassing can be used, as long as steel that meets the target composition can be produced.

[0042] The molten steel that has passed smelting is continuously cast and rolled into billets of predetermined specifications. In some embodiments of the present invention, the diameter of the billet of predetermined specifications is 70-80 mm, and the target diameter of the prepared grinding steel ball is 110-150 mm. The diameter of the billet and the target diameter of the steel ball result in an axial forging ratio of 1.5-3.0 for the steel segment to the steel ball blank. The axial forging ratio is calculated according to the following formula: K L =L0 / L1, where L0 represents the original axial length before forging and L1 represents the final axial length after forging. For example, if a 70mm diameter bar is forged into a 110mm diameter ball, the length of the cut steel segment is 181mm, and the axial forging ratio of the forging is 1.64.

[0043] The billet diameter is set to match the subsequent forging process, ensuring the preset axial forging ratio, effectively breaking down cast dendrites and coarse carbides, refining the grains, while avoiding forming defects such as folding and cracking caused by an excessive forging ratio. Simultaneously, the suitable billet diameter fits well with the die cavity, ensuring uniform metal flow, a smooth, flash-free steel ball surface, and a dense internal structure. This provides a good initial microstructure for subsequent heat treatment to obtain a uniform tempered martensite and bainite multiphase structure. The billet length can be 8~10m.

[0044] In some embodiments of the present invention, the final rolling temperature is 800~850°C. Controlling the final rolling temperature to this temperature allows the rolling deformation to end in the austenite recrystallization zone, resulting in uniform and fine austenite grains. This effectively suppresses the formation of a surface oxide decarburized layer and reduces subsequent processing allowances.

[0045] In step S2, the billet is subjected to segmented controlled cooling. Specifically, after rolling, a walking beam cooling bed can be used for segmented forced air cooling. The rolled billet is immediately fed into the walking beam cooling bed, where it moves and rotates along with the cooling bed to ensure uniform cooling along its entire length and circumference.

[0046] In step S21, the billet is cooled to a first temperature using a first cooling rate, the first cooling rate being higher than the critical cooling rate of pearlite, and the first temperature being higher than the bainite transformation start temperature.

[0047] Specifically, in some embodiments of the present invention, the billet is cooled to a first temperature by forced convection cooling with strong air at the front of the cooling bed. The fan speed is controlled at 4.0~6.0 m / s, corresponding to a cooling rate of about 1.5~2.5℃ / s, cooling to about 350~400℃. This cooling rate is higher than the critical cooling rate for pearlite transformation. Combined with the high hardenability design, there is no pearlite transformation throughout the process, and all the supercooled austenite is maintained.

[0048] In step S22, the billet is cooled to room temperature using a second cooling rate, which is within the bainite transformation cooling rate range.

[0049] Specifically, in some embodiments of the present invention, the billet is cooled to room temperature by a slow, gentle airflow cooling process in the rear section of a cooling bed, with the fan speed controlled at 1.0~2.0 m / s, corresponding to a cooling rate of approximately 0.3~0.8 °C / s. This cooling rate falls within the bainitic transformation cooling rate range, resulting in bainitic phase transformation along the entire length and cross-section of the billet. Bainite first nucleates at the original austenite grain boundaries and grows along the grain boundaries into the grains in a self-catalytic manner, forming lath or acicular bainite structures. As the bainite laths extend and thicken, they continuously intersect within the grains, cutting and separating the originally coarse austenite grains into multiple isolated small regions. The residual austenite after being divided by bainite is completely enclosed between the fine bainite networks, losing the space for continuous growth. When subsequent reheating and quenching are performed, these divided micro-austenite regions, due to their high interfacial energy and high nucleation point density, will form a large number of fine austenite grains, thereby achieving the effect of pre-refining the grains. Ultimately, the billet obtains a bainite-dominated microstructure with numerous subgrain boundaries, which provides fine primary grains for the martensite / bainite duplex structure after final heat treatment, significantly improving the strength and toughness matching of large-sized steel balls.

[0050] In step S3, the billet is cut into equal volume segments according to the target diameter of the steel ball. The steel segments are heated to austenitize and then forged into steel ball blanks at a third temperature, which is in the two-phase region of austenite and ferrite.

[0051] Specifically, in some embodiments of the present invention, the billet is first cut into equal volume segments according to the target diameter, with a diameter of 120mm as an example for illustrative purposes.

[0052] The volume of the steel ball is calculated according to the following formula (1): Formula (1), Where V 球 R represents the volume of the steel ball of the target size, and R represents the radius of the steel ball of the target size.

[0053] The volume of the cylindrical blank obtained after cutting the bar billet into segments is calculated according to the following formula (2): Formula (2), Where V 柱 The value represents the volume of the cylindrical steel segment obtained by cutting, r represents the radius of the steel segment (i.e., the billet), and L represents the length of the steel segment.

[0054] According to the law of volume conservation, the volume before and after forging is equal, that is, formula (1) equals formula (2). If the preset diameter of the steel ball is 120mm, when a 70mm diameter billet is used, the cutting length is 235mm, and the corresponding axial forging ratio is 1.96; when an 80mm diameter billet is used, the cutting length is 180mm, and the corresponding axial forging ratio is 1.5.

[0055] The steel section is heated to austenitize at a temperature of 900–950°C for 5–10 minutes. This process ensures that the alloy carbides are fully dissolved in the austenite while preventing abnormal grain growth, resulting in a uniform, fine-grained austenitic microstructure. This temperature range guarantees effective solid solution of alloying elements such as chromium, molybdenum, and vanadium, improving hardenability, while avoiding excessively high temperatures that could lead to austenite grain coarsening or severe surface decarburization. This provides a foundation for subsequent quenching to obtain uniform tempered martensite. The steel section is then forged into a steel ball blank at a third temperature, which falls within the austenite-ferrite two-phase region.

[0056] By comprehensively controlling the billet diameter, segment length, axial forging ratio, and forging temperature, the initial microstructure is broken down by large deformation, and more crystal defects are introduced to fully refine the grains, while ensuring stable forming and high dimensional accuracy. During pressure forging, forging occurs in the α+γ two-phase region. Ferrite has poorer deformation capacity compared to austenite. Introducing ferrite increases the number of defects in the deformed austenite and ferrite. High-density defects and distortion promote recrystallization to form more austenite, refining the austenite grain size and laying the foundation for obtaining the final refined microstructure.

[0057] In some embodiments of the present invention, the third temperature is 740~760°C. Forging is performed at this temperature, where a ferrite phase exists in the steel, introducing more defects. After forging, the temperature is raised to 780~800°C for re-austenitization. Due to the higher accumulation of defects from the previously deformed ferrite, the distortion energy promotes recrystallization into austenite, refining the austenite grain size. This achieves further austenite grain division, refining the microstructure after quenching.

[0058] In step S4, the steel ball blank is quenched in water. The surface temperature of the steel ball is controlled to reach a fourth temperature, which is between the start and end temperatures of the martensitic transformation. In this step, constant-temperature water is used, with the temperature controlled between 25 and 40°C. The water temperature can be controlled by using a water bath in conjunction with flowing water. During quenching, the surface cools rapidly, forming a structure dominated by fine laths or needle-like martensite, which has high hardness and good wear resistance. The core cools slowly, with a high content of residual austenite, which can balance the thermal stress and structural stress of the surface martensitic transformation. If the exit water temperature is lower than the end temperature of the martensitic transformation, martensitic transformation will continue to occur inside the steel ball, leading to volume expansion. Since the surface layer of the steel ball has completely transformed into hard and brittle martensite with low plasticity, it cannot alleviate the structural stress caused by the volume expansion of the phase transformation through local plastic deformation; at the same time, the temperature difference between the core and the surface layer will also induce thermal stress. When the superposition of structural stress and thermal stress results in excessive stress, quenching cracking will occur.

[0059] This invention controls the water temperature during the quenching of steel ball blanks to be between the martensitic transformation start and end temperatures on the surface of the steel ball. This temperature falls within the incomplete martensitic transformation range, ensuring controllable surface martensitic transformation and low stress, thus preventing cracking during quenching. The core temperature is high, resulting in incomplete martensitic transformation, a high content of retained austenite, and a low volume fraction of martensite in the core. During subsequent low-temperature tempering heat treatment, the retained austenite enriched in the core transforms into bainite. This process eliminates structural stress, counteracts martensitic expansion stress, and improves toughness, making the steel ball less prone to cracking even under strong impacts during service. Furthermore, due to the small initial austenite grain size, the numerous nucleation sites during bainite nucleation and autocatalytic growth from austenite grain boundaries result in small bainite grains with many grain boundaries, filling the strength gap caused by insufficient martensite in the core and achieving consistent surface and core hardness with a difference of less than 2 HRC. Simultaneously, the refined microstructure and small grain size also improve toughness and strength.

[0060] In some embodiments of the present invention, the fourth temperature is 130~170°C. This temperature allows for controllable martensitic transformation and low stress. If the temperature is too high, the surface martensitic transformation will be insufficient; if the temperature is too low, cracking is likely to occur.

[0061] In step S5, the quenched steel ball blank is heated for tempering. In some embodiments of the present invention, the tempering temperature is 200~250℃, and the holding time is 5~10h. Tempering eliminates quenching thermal stress and phase transformation expansion stress. During tempering, the residual austenite in the core is stably transformed into bainite, while the surface layer only undergoes martensite tempering stabilization. The final surface layer is mainly composed of fine tempered martensite, while the core is mainly composed of tempered martensite and bainite. Due to the small original austenite grain size, the resulting surface and core microstructures are fine, with small grain sizes and numerous grain boundaries, filling the strength gap caused by insufficient martensite in the core and achieving consistent surface and core hardness with a difference of less than 2HRC. Simultaneously, due to the refined microstructure and small grain size, its toughness and strength are also improved.

[0062] The method of the present invention will be further described and illustrated below with reference to embodiments.

[0063] Example 1 The steel ball prepared in this embodiment comprises the following components by mass percentage: C: 0.73%, Si: 0.35%, Mn: 0.95%, Cr: 0.65%, Ni: 0.35%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities. The target diameter of the steel ball is 120 mm.

[0064] The steel balls were smelted according to the target composition and continuously cast and rolled into billets with a diameter of 70 mm. The billets underwent segmented controlled cooling, specifically: cooling the billets to 375°C at 2°C / s, and then cooling them to room temperature at 0.5°C / s. The billets were then cut into segments of 235 mm in length (axial forging ratio of 1.96) according to the target diameter of the steel balls. The steel segments were heated to 930°C, held for 8 minutes, and then forged into steel ball blanks at 750°C. The steel ball blanks were quenched in water at 30°C, and removed from the water when the surface temperature reached 150°C. The quenched steel ball blanks were then heated to 230°C, held for 8 hours, and tempered.

[0065] The mechanical properties and microstructure of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 56 HRC, and the core hardness is approximately 55 HRC, with the hardness difference between the surface and core controlled within 1 HRC; the surface impact energy is 27 J, and the core impact energy is 29 J. It does not crack during quenching, and has undergone 4500 drop tests without cracking. It exhibits no cracking during quenching, tempering, and storage, and has remained crack-free after 3 months of grinding service; the yield strength is approximately 1890 MPa, and the tensile strength is approximately 2100 MPa (e.g., ...). Figure 2 (As shown).

[0066] Figure 3 A scanning electron microscope image of the surface tissue of a steel ball according to Embodiment 1 of the present invention is shown. Figure 4 The image shows a scanning electron microscope (SEM) image of the core microstructure of a steel ball according to Embodiment 1 of the present invention. The microstructure of the surface layer and the core layer are compared. The martensite laths in the surface layer are smaller, while the corresponding martensite laths in the core layer are coarser than those in the surface layer, but the overall microstructure is more uniform and finer.

[0067] Figure 5 A photograph of the average grain size test of the steel ball according to Embodiment 1 of the present invention is shown. The austenite grain size of the parent phase is refined. According to ASTM E2627, the average grain size is 10~12μm, which is relatively small.

[0068] Example 2 The steel ball prepared in this embodiment comprises the following components by mass percentage: C: 0.68%, Si: 0.25%, Mn: 0.85%, Cr: 0.55%, Ni: 0.3%, Mo: 0.04%, V: 0.06%, with the remainder being Fe and unavoidable impurities. The target diameter of the steel ball is 110 mm.

[0069] The steel balls were smelted according to the target composition and continuously cast and rolled into billets with a diameter of 70 mm. The billets underwent segmented controlled cooling, specifically: cooling to 350°C at 1.5°C / s, and then cooling to room temperature at 0.3°C / s. The billets were then cut into segments of 181 mm in length (axial forging ratio 1.65) according to the target diameter of the steel balls. The steel segments were heated to 900°C, held for 10 minutes, and then forged into steel ball blanks at 740°C. The steel ball blanks were quenched in water at 25°C, and removed from the water when the surface temperature reached 130°C. The quenched steel ball blanks were then heated to 200°C, held for 10 hours, and tempered.

[0070] The mechanical properties of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 54HRC, the core hardness is about 52HRC, and the hardness difference between the surface and the core is controlled within 2HRC; the surface impact energy is about 26J, the core impact energy is 29J, no cracking occurs during the quenching process, the single ball drop test reaches 4500 times without cracking, no cracking occurs during quenching, tempering and storage, and no cracking occurs after 3 months of grinding service; the yield strength is about 1810MPa, and the tensile strength is about 2030MPa.

[0071] Example 3 The steel ball prepared in this embodiment comprises the following components by mass percentage: C: 0.70%, Si: 0.30%, Mn: 0.90%, Cr: 0.60%, Ni: 0.32%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities. The target diameter of the steel ball is 120 mm.

[0072] The steel balls are smelted according to the target composition and continuously cast and rolled into billets with a diameter of 80 mm. The billets undergo segmented controlled cooling, specifically: cooling to 360 °C at 1.8 °C / s, and then cooling to room temperature at 0.4 °C / s. The billets are then cut into segments of 180 mm in length (axial forging ratio of 1.5) according to the target diameter of the steel balls. The steel segments are heated to 920 °C, held for 8 minutes, and then forged into steel ball blanks at 750 °C. The steel ball blanks are quenched in water at 30 °C, and removed from the water when the surface temperature reaches 140 °C. The quenched steel ball blanks are then heated to 220 °C, held for 8 hours, and tempered.

[0073] The mechanical properties of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 55HRC, the core hardness is about 53HRC, and the hardness difference between the surface and the core is controlled within 2HRC; the surface impact energy is 26J, the core impact energy is 28J, no cracking occurs during the quenching process, and no cracking occurs after a single ball drop test of 4500 times. No cracking occurs during the entire process of quenching, tempering, storage and grinding service; the yield strength is 1850MPa, and the tensile strength is 2080MPa.

[0074] Example 4 The steel ball prepared in this embodiment comprises the following components by mass percentage: C: 0.75%, Si: 0.40%, Mn: 1.0%, Cr: 0.70%, Ni: 0.37%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities. The target diameter of the steel ball is 140 mm.

[0075] The steel balls were smelted according to the target composition and continuously cast and rolled into billets with a diameter of 80 mm. The billets underwent segmented controlled cooling, specifically: cooling the billets to 380°C at 2.2°C / s, and then cooling them to room temperature at 0.6°C / s. The billets were then cut into segments of 285 mm in length (axial forging ratio 2.04) according to the target diameter of the steel balls. The steel segments were heated to 930°C, held for 8 minutes, and then forged into steel ball blanks at 750°C. The steel ball blanks were quenched in water at 35°C, and removed from the water when the surface temperature reached 160°C. The quenched steel ball blanks were then heated to 240°C, held for 6 hours, and tempered.

[0076] The mechanical properties of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 56HRC, the core hardness is 54HRC, and the hardness difference between the surface and the core is controlled within 2HRC; the surface impact energy is 26J, the core impact energy is 28J, no cracking occurs during the quenching process, and no cracking occurs after a single ball drop test of 4500 times. No cracking occurs during the entire process of quenching, tempering, storage, and grinding service; the yield strength is higher than 1800MPa, and the tensile strength is higher than 2000MPa.

[0077] Example 5 The steel ball prepared in this embodiment comprises the following components by mass percentage: C: 0.78%, Si: 0.45%, Mn: 1.05%, Cr: 0.75%, Ni: 0.4%, Mo: 0.06%, V: 0.06%, with the remainder being Fe and unavoidable impurities. The target diameter of the steel ball is 150 mm.

[0078] The steel balls were smelted according to the target composition and continuously cast and rolled into billets with a diameter of 80 mm. The billets underwent segmented controlled cooling, specifically: cooling to 400°C at 2.5°C / s, and then cooling to room temperature at 0.8°C / s. The billets were then cut into segments of 351 mm in length (axial forging ratio 2.34) according to the target diameter of the steel balls. The steel segments were heated to 950°C, held for 10 minutes, and then forged into steel ball blanks at 760°C. The steel ball blanks were quenched in water at 40°C, and removed from the water when the surface temperature reached 170°C. The quenched steel ball blanks were then heated to 250°C, held for 5 hours, and tempered.

[0079] The mechanical properties of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 56HRC, the core hardness is 54HRC, and the hardness difference between the surface and the core is controlled within 2HRC; the surface impact energy is 25J, the core impact energy is 28J, no cracking occurs during the quenching process, and no cracking occurs after a single ball drop test of 4500 times. No cracking occurs during the entire process of quenching, tempering, storage and grinding service; the yield strength is higher than 1800MPa, and the tensile strength is higher than 2000MPa.

[0080] Comparative Example 1 The steel balls prepared in this comparative example have the same composition and specifications as those prepared in Example 1, and the preparation process is also basically the same. The main difference between the two is that Comparative Example 1 did not perform segmented controlled cooling after continuous casting and rolling into a billet. Instead, it directly used the residual heat of the billet to forge into balls and then water quenched them. Its cutting, forging, quenching, and tempering processes are all the same as those in Example 1.

[0081] The mechanical properties and microstructure of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 54 HRC, and the core hardness is 49 HRC; the surface impact energy is 15 J, and the core impact energy is 18 J. Figure 6 Photographs of the average grain size of the steel balls in Comparative Example 1 are shown. The parent phase austenite grains are coarse, with an average grain size of approximately 40–50 μm according to ASTM E2627, significantly higher than the grain size in Example 1. This coarse austenite grain size is due to the lack of controlled cooling.

[0082] Comparative Example 2 The steel balls prepared in this comparative example have the same composition and specifications as those prepared in Example 1, and the preparation process is also basically the same. The main difference between the two is that after cutting, the forging temperature of Comparative Example 2 is 790°C, and the subsequent quenching and tempering processes are the same as those in Example 1.

[0083] The mechanical properties and microstructure of the prepared steel balls were tested, and the results are as follows: The surface hardness reaches 52HRC, and the core hardness is 48HRC; the surface impact energy is 18J, and the core impact energy is 20J. Figure 7 Photographs of the average grain size of the steel ball in Comparative Example 2 are shown. The parent phase austenite grains are coarse, with an average grain size of approximately 30–40 μm according to ASTM E2627, significantly higher than the grain size in Example 1. The coarsening of the austenite grains due to excessively high temperatures during forging resulted in a larger final grain size and insufficient hardness and toughness.

[0084] Comparative Example 3 The steel balls prepared in this comparative example have the same composition and specifications as those prepared in Example 1, and the preparation process is also basically the same. The main difference between the two is that in Comparative Example 3, the surface temperature of the steel balls is controlled to reach 100°C before being removed from the water during quenching.

[0085] Cracking occurred during the quenching process due to the low outlet water temperature. This may be because the quenching termination temperature was too low, resulting in a high degree of martensite transformation in the core. The superposition of structural stress and thermal stress led to excessive stress, causing quenching cracks.

[0086] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the disclosed embodiments of the present invention is limited to these examples; within the framework of the embodiments of the present invention, the technical features of the above embodiments or different embodiments can also be combined, and there are many other variations of different aspects of the embodiments of the present invention as described above, which are not provided in detail for the sake of brevity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the embodiments of the present invention should be included within the protection scope of the embodiments of the present invention.

Claims

1. A grinding steel ball with a diameter of 110 mm or more, characterized in that, The steel ball comprises the following components by mass percentage: C: 0.68%~0.78%, Si: 0.25%~0.45%, Mn: 0.85%~1.05%, Cr: 0.55%~0.75%, Ni: 0.3%~0.4%, Mo: 0.04%~0.06%, V: 0.04%~0.06%, with the remainder being Fe and unavoidable impurities. The surface microstructure of the steel ball is tempered martensite, and the core microstructure comprises tempered martensite and bainite. The steel ball is prepared by a method comprising the following steps: The steel balls are smelted according to the target composition and continuously cast and rolled into billets of predetermined specifications. The billet is subjected to segmented controlled cooling, wherein the segmented controlled cooling includes: The billet is cooled to a first temperature at a first cooling rate, the first cooling rate being higher than the critical cooling rate for pearlite transformation, and the first temperature being higher than the bainite transformation start temperature, wherein the first cooling rate is 1.5~2.5℃ / s and the first temperature is 350~400℃. The billet is cooled to room temperature at a second cooling rate, which is within the bainite transformation cooling rate range, and the second cooling rate is 0.3~0.8℃ / s; According to the target diameter of the steel ball, the billet is cut into equal volume segments, the steel segments are heated to austenitize and then forged into steel ball blanks at a third temperature. The third temperature is in the two-phase region of austenite and ferrite, and the third temperature is 740~760℃. The steel ball blank is placed in water for quenching. The steel ball surface temperature is controlled to reach a fourth temperature and then removed from the water. The fourth temperature is between the martensitic transformation start temperature and the martensitic transformation end temperature, and the fourth temperature is 130~170℃. The quenched steel ball blank is then heated and tempered.

2. The grinding steel ball with a diameter of 110 mm or more according to claim 1, characterized in that, The steel ball comprises the following components by mass percentage: C: 0.73%, Si: 0.35%, Mn: 0.95%, Cr: 0.65%, Ni: 0.35%, Mo: 0.05%, V: 0.05%, with the remainder being Fe and unavoidable impurities.

3. A method for preparing grinding steel balls with a diameter of 110 mm or more, characterized in that, The method is used to prepare the grinding steel ball as described in claim 1 or 2, and the method includes the following steps: The steel balls are smelted according to the target composition and continuously cast and rolled into billets of predetermined specifications. The billet is subjected to segmented controlled cooling, wherein the segmented controlled cooling includes: The billet is cooled to a first temperature at a first cooling rate, the first cooling rate being higher than the critical cooling rate for pearlite transformation, and the first temperature being higher than the bainite transformation start temperature, wherein the first cooling rate is 1.5~2.5℃ / s and the first temperature is 350~400℃. The billet is cooled to room temperature at a second cooling rate, which is within the bainite transformation cooling rate range, and the second cooling rate is 0.3~0.8℃ / s; According to the target diameter of the steel ball, the billet is cut into equal volume segments, the steel segments are heated to austenitize and then forged into steel ball blanks at a third temperature. The third temperature is in the two-phase region of austenite and ferrite, and the third temperature is 740~760℃. The steel ball blank is placed in water for quenching. The steel ball surface temperature is controlled to reach a fourth temperature and then removed from the water. The fourth temperature is between the martensitic transformation start temperature and the martensitic transformation end temperature, and the fourth temperature is 130~170℃. The quenched steel ball blank is then heated and tempered.

4. The method for preparing grinding steel balls with a diameter of 110 mm or more according to claim 3, characterized in that, The final rolling temperature is 800~850℃.

5. The method for preparing grinding steel balls with a diameter of 110 mm or more according to claim 3, characterized in that, The diameter of the pre-defined bar billet is 70-80 mm, and the target diameter of the steel ball is 110-150 mm. The diameter of the bar billet and the target diameter of the steel ball make the axial forging ratio of the steel segment to the steel ball blank 1.5-3.

0.

6. The method for preparing grinding steel balls with a diameter of 110 mm or more according to claim 5, characterized in that, The austenitizing temperature of the steel segment is 900~950℃, and the holding time is 5~10min.

7. The method for preparing grinding steel balls with a diameter of 110 mm or more according to claim 3, characterized in that, The tempering treatment is performed at a temperature of 200~250℃ for 5~10 hours.

Citation Information

Patent Citations

  • Large-diameter forged wear-resisting steel ball special for mine and preparation method thereof

    CN107739986A

  • Steel for high-carbon wear-resisting ball material and production method thereof

    CN103627955A

  • Steel for large-diameter grinding balls and preparation method of steel

    CN104762562A